Penyuluhan Pengelolaan Keuangan Daerah Berdasarkan Undang-Undang No 1 Tahun 2022 Mengenai HKPD Di Fakultas Ekonomi Universitas Sam Ratulangi: Regional Financial Management Training Based on Law No. 1 of 2022 (HKPD) at the Faculty of Economics, Sam Ratulangi University - Masinambow, Vecky A. J.; Kalangi, Josep Bintang; Mandeij.,SE.M.Si, Dennij; Sari , Greydi Normala; Lumi, Angela N.M (Sam Ratulangi University, 2025)
Effective and transparent financial management between the Central Government and Regional Governments is essential in creating good and sustainable governance. This community outreach activity aims to provide a deeper understanding of Law No. 1 of 2022, which regulates the scope of fiscal relations between the central and regional governments. The program involves government officials, academics, and relevant stakeholders to enhance their knowledge of the mechanisms of intergovernmental fiscal transfers, which include: (1) granting sources of local revenue through taxes and levies; (2) management of transfers to regions (TKD); (3) management of regional expenditures; (4) authorization to conduct regional financing; and (5) the implementation of national fiscal policy synergy. ABSTRAK Pengelolaan keuangan yang efektif dan transparan antara Pemerintah Pusat dan Pemerintah Daerah (Pemda) sangat penting dalam rangka menciptakan pemerintahan yang baik dan berkelanjutan. Penyuluhan ini bertujuan untuk memberikan pemahaman yang lebih mendalam mengenai Undang-Undang Nomor 01 Tahun 2022 UU ini mengatur mengenai lingkup hubungan keuangan antara pemerintah pusat dan pemerintah daerah. Kegiatan ini akan melibatkan aparatur pemerintahan, akademisi, dan masyarakat umum yang berkepentingan untuk meningkatkan pengetahuan mengenai mekanisme dana perimbangan, yang meliputi: 1) pemberian sumber penerimaan daerah berupa pajak dan retribusi; 2) pengelolaan Transfer ke Daerah/TKD; 3) pengelolaan belanja daerah; 4) pemberian kewenangan untuk melakukan pembiayaan daerah; dan 5) pelaksanaan sinergi kebijakan fiskal nasional. Penyuluhan ini akan dilaksanakan dengan metode ceramah yang diselingi dengan diskusi interaktif, yang memberikan kesempatan bagi peserta untuk membahas berbagai tantangan dalam implementasi UUD HKPD dan mencari solusi atas masalah yang dihadapi daerah dalam pengelolaan keuangan. Melalui kegiatan ini, target yang diharapkan peserta dapat meningkatkan kapasitas dalam pengelolaan anggaran daerah secara efisien, mengoptimalkan penggunaan dana perimbangan, dan meningkatkan transparansi dalam pengelolaan keuangan daerah untuk kesejahteraan masyarakat. Luaran hasil PKM_K2 adalah berupa satu artikel ilmiah yang akan dipublikasi pada media online dan membuat video youtube. The activity was conducted through a lecture method combined with interactive discussions, providing participants the opportunity to explore various challenges in implementing the Fiscal Relations Law (HKPD) and to identify practical solutions for improving regional financial management. Through this activity, participants are expected to strengthen their capacity in managing local budgets more efficiently, optimizing the use of fiscal transfer funds, and improving transparency and accountability in regional financial governance to promote public welfare. The expected outcomes of this PKM_K2 program include a scientific article published in an online media outlet and a YouTube video documenting and disseminating the activity results. Keywords: Fiscal Relations Law, Intergovernmental Transfer, DAU, DAK, Local Taxation